Sugammadex versus neostigmine for neuromuscular blockade reversal in outpatient surgeries: A randomized controlled trial to evaluate efficacy and associated healthcare cost in an academic center - Fiorda Diaz, Juan; Echeverria-Villalobos, Marco; Esparza Gutierrez, Alan; Dada, Olufunke; Stoicea, Nicoleta; Ackermann, Wiebke; Abdel-Rasoul, Mahmoud; Heard, Jarrett; Uribe, Alberto; Bergese, Sergio D. (Frontiers in Medicine, 2022)
Introduction Neuromuscular blockade is an essential component of the general anesthesia as it allows for a better airway management and optimal surgical conditions. Despite significant reductions in extubation and OR readiness-for-discharge times have been associated with the use of sugammadex, the cost-effectiveness of this drug remains controversial. We aimed to compare the time to reach a train-of-four (TOF) response of ≥0.9 and operating room readiness for discharge in patients who received sugammadex for moderate neuromuscular blockade reversal when compared to neostigmine during outpatient surgeries under general anesthesia. Potential reduction in time for OR discharge readiness as a result of sugammadex use may compensate for the existing cost-gap between sugammadex and neostigmine. Methods We conducted a single-center, randomized, double arm, open-label, prospective clinical trial involving adult patients undergoing outpatient surgeries under general anesthesia. Eligible subjects were randomized (1:1 ratio) into two groups to receive either sugammadex (Groups S), or neostigmine/glycopyrrolate (Group N) at the time of neuromuscular blockade reversal. The primary outcome was the time to reverse moderate rocuronium-induced neuromuscular blockade (TOF ratio ≥0.9) in both groups. In addition, post-anesthesia care unit (PACU)/hospital length of stay (LOS) and perioperative costs were compared among groups as secondary outcomes. Results Thirty-seven subjects were included in our statistical analysis (Group S= 18 subjects and Group N= 19 subjects). The median time to reach a TOF ratio ≥0.9 was significantly reduced in Group S when compared to Group N (180 versus 540 seconds; p = 0.0052). PACU and hospital LOS were comparable among groups. Postoperative nausea and vomiting was the main adverse effect reported in Group S (22.2% versus 5.3% in Group N; p = 0.18), while urinary retention (10.5%) and shortness of breath (5.3%) were only experienced by some patients in Group N. Moreover, no statistical differences were found between groups regarding OR/anesthesia, PACU, and total admission costs. Discussion Sugammadex use was associated with a significantly faster moderate neuromuscular blockade reversal. We found no evidence of increased perioperative costs associated with the use of sugammadex in patients undergoing outpatient surgeries in our academic institution. Clinical trial registration [https://clinicaltrials.gov/] identifier number [NCT03579589].